IMPLEMENTASI KEBIJAKAN PENGANGKATAN MUHAMMAD RUDI SEBAGAI EX-OFFICIO KEPALA BADAN PENGUSAHAAN (BP) BATAM (STUDI KASUS PEMBANGUNAN INFRASTRUKTUR PELABUHAN PENUMPANG DI KOTA BATAM TAHUN 2021) - Kurnia, Ditri Prima; ', Ishak (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The Ex-Officio Policy is applied in Batam City to the Batam Authority Government agency which is currently transformed into the Batam Concession Agency or known as BP Batam. This policy is an agenda set by the President based on PP No. 62 of 2019, which has been going on for 5 years. In this writing, the author focuses on the implementation of the Ex-Officio policy on the development of domestic passenger port infrastructure in Batam City in 2021. The purpose of the study was to determine the implementation of Ex-Officio policy on he development of domestic passenger port infrastructure in Batam City carried out by the Batam Business Agency (BP) based on 6 indicators of policy implementation from George C. Edward III, namely communication, resources, disposition, and bureaucratic structure. The research method used in this study is a descriptive research method with a qualitative approach. Data collection techniques through interviews and documentation studies. The results of this study show that the Ex-Officio policy on the development of domestic passenger port infrastructure in Batam City in 2021 does not significantly affect its objectives, namely in the context of developing the Batam Free Trade Zone and Free Port regarding activities related to public infrastructure development and public interest when viewed from the e-eTick policy implementation indicators. However, it has been implemented in accordance with policy principles, namely objective, agreement-oriented, and accountable, it's just that there is no transparency, as well as effectiveness and efficiency, especially in the port infrastructure development process. This policy also has an impact that can be felt now and future impacts. The hope in the future is that there must be an acceleration of port infrastructure development, especially domestic ports in an equitable and equitable manner so that there is no more inequality in the development between assets owned by BP Batam, as well as transparency in every process of implementing infrastructure development activities and programs. Keywords: Port Infrastructure Development, Ex-Officio Policy, Batam Business Agency (BP)